PERISTIWA-PERISTIWA YANG MEMBUAT BAHAGIA - Harmaini Harmaini; Alma Yulianti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2014)
This research aimed to explore the events that experienced and made the teens happy. The survey method was conducted with a total sample of 51 boys and 159 girls of high school students in Pekanbaru City. The instrument was an open-ended question and the data processed by descriptive analysis. Based on the research results, the three major components that events make teens happy namely (1) Relation by 55.7% includes events related to parents, family and peers. (2) Personal affective by 34.7% of the events associated with the opposite sex, affection, the psychological benefits, hobbies, etc., and (3) achievement by 24.7% includes events associated with achievement, graduation, ability to complete the task, and satisfactory result.